The Effect of Competitive Strategy and Product Quality on Business Performance Study On: Unilever Indonesia Tbk - Cici Dwi Vidiastutik; Kartono Kartono (Jurnal Indonesia Sosial Sains, 2024)
Currently, in the global market era, many daily necessities are circulating in the world goods market domestic and foreign products. Many companies are developing in Indonesia, both domestic companies and foreign investment companies. One of them is Unilever Indonesia which operates in the primary consumer sector. This research aims to describe efforts to create the influence of competitive strategy and product quality on business performance at Unilever Indonesia Tbk. The urgency of research is to fulfill assignments for the Strategic Management course and as a requirement to take the Final Semester Examination. This research is intended for readers as supporting material for further research in the future and is also useful for writers to develop the process of creating scientific work. This research uses a descriptive quantitative approach method with Explanatory Research research, using annual financial data for the last 3-year period. This method aims to find variable relationships that exist in a community. Using company financial reports to determine the results and influence of competitive strategy and product quality on company sales over several decades and determine the effectiveness of company strategy in the company's business performance. This research was created based on references from several journals by previous researchers with variables that are closely related to the title of the research created by the author.